PENGARUH KOMPARABILITAS LAPORAN KEUANGAN, KUALITAS PENGUNGKAPAN, DAN KENDALA PEMBIAYAAN TERHADAP KEPEMILIKAN KAS PERUSAHAAN - Ziana Trifinta Rizqiani; Faisal Faisal (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of financial statement comparability as a qualitative feature of financial reporting on cash holdings and the mediating role of disclosure quality and financing constraints. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2020. The research sample was 280 companies. This research used multiple regression in analyzing the data. The results show that financial reporting comparability has a significant negative effect on corporate cash holdings. The results also show that disclosure quality and financing constraints have mediating role in the relationship between accounting comparability and cash holdings.